Using magnetic data for estimating the location of lateral boundaries and the depth of the shallow salt dome of Aji-Chai, East Azerbaijan Province, Iran - Ahmad Alvandi; Reza Ghanati (International Journal of Mining and Geo-Engineering, 2023)
Magnetic data play a significant role in the interpretation of various geologic structures using depth estimation methods and edge detection filters. In this study, we applied methods based on directional derivatives such as tilt-depth (TD), signum transform (ST), source distance (SD) and classical Euler deconvolution (ED) to estimate the depth of the magnetic sources. Moreover, to enhance the edges of magnetic field anomalies, we utilize the total horizontal derivative (THD), analytical signal (AS), tilt angle (TA), theta map (TM), hyperbolic tilt angle (HTA), the tilt angle of horizontal derivative (TAHG), and logistic function of total horizontal gradient (LTHD). These algorithms are tested on a synthetic magnetic model with noise and free noise to understand their performance. Since the edge detection filters are sensitive to noise, we carry out an upward continuation (UC) filter before the reduction of data to magnetic the pole to reduce the noise effect. After comparing the efficiency of the approaches in estimating the depth and horizontal lateral boundaries, these methods were applied to the data surveyed from the Aji-Chai salt dome in East Azerbaijan Province, Iran. The results obtained by the depth determination methods were compared with the drilling report of Iran’s geological survey and three-dimensional classical Euler deconvolution method.